Answers

2015-12-10T07:27:07+08:00

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
To solve for the equation
3 - 7x + 1/3 = 4 - (x + 2/3)
First we will remove parenthesis by distributing negative sign to the terms inside the parenthesis
3 - 7x + 1/3 = 4 - x - 2/3
Transpose x to the left side and 1 & 1/3 to the right side
-7x + x = 4 - 2/3 - 3 - 1/3
Let's add the similar terms now
-6x = 1 - 3/3
-6x = 1 - 1
-6x = 0
-6x / -6 = 0 / -6
x = 0

Therefore, the solution of the equation
3 - 7x + 1/3 = 4 - (x + 2/3) is x = 0





0